2009
DOI: 10.1007/s00159-009-0026-0
|View full text |Cite
|
Sign up to set email alerts
|

Radio and millimeter continuum surveys and their astrophysical implications

Abstract: We review the statistical properties of the main populations of radio sources, as emerging from radio and millimeter sky surveys. Recent determinations of local luminosity functions are presented and compared with earlier estimates still in widespread use. A number of unresolved issues are discussed. These include: the (possibly luminositydependent) decline of source space densities at high redshifts; the possible dichotomies between evolutionary properties of low-versus high-luminosity and of flat-versus stee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
244
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(260 citation statements)
references
References 351 publications
(407 reference statements)
16
244
0
Order By: Relevance
“…Physically, the amplitudes of our source corrections are reasonable; at 143 GHz we measurê S 4 143 = (1.3±0.6)×10 −12 µK 4 . From the radio point-source model of De Zotti et al (2010), this corresponds to an effective flux cut of approximately 150 mJy at this frequency, roughly comparable to that expected for the S /N > 5 cut we make when masking sources in our fiducial analysis (Planck Collaboration XXVIII 2014). The shot noise measured at 217 GHz is lower, as expected given the smaller contribution from radio sources, witĥ S 4 217 = (0.4 ± 0.4) × 10 −12 µK 4 .…”
Section: Point Source Correctionsupporting
confidence: 67%
“…Physically, the amplitudes of our source corrections are reasonable; at 143 GHz we measurê S 4 143 = (1.3±0.6)×10 −12 µK 4 . From the radio point-source model of De Zotti et al (2010), this corresponds to an effective flux cut of approximately 150 mJy at this frequency, roughly comparable to that expected for the S /N > 5 cut we make when masking sources in our fiducial analysis (Planck Collaboration XXVIII 2014). The shot noise measured at 217 GHz is lower, as expected given the smaller contribution from radio sources, witĥ S 4 217 = (0.4 ± 0.4) × 10 −12 µK 4 .…”
Section: Point Source Correctionsupporting
confidence: 67%
“…Assuming a Poisson distribution (clustering effects are reduced to negligible values by the very broad luminosity function of radio sources, e.g., Toffolatti et al 2005;de Zotti et al 2010) and simply scaling As it is apparent, the two values are very close to each other, within the 1σ level calculated for the overall population in the two sky areas considered here, and well inside the 1σ normalized Poisson error bars. We also checked that at flux densities below about 0.9-1.0 Jy statistically more relevant deviations from a uniform distribution begin to appear.…”
Section: Number Countssupporting
confidence: 68%
“…Since it is inconsistent with known radio source populations (e.g. De Zotti et al 2010;Padovani 2011), it must, if confirmed, be caused by another population. For example, the radio emission could be caused by dark matter annihilation (Fornengo et al 2011), in which case the emission would trace the dark matter distribution of cluster galaxies, resulting in a scale size of ß arcmin.…”
Section: Are There Undiscovered Populations Of Radiomentioning
confidence: 95%